Bouveret Syndrome: Rare but Quite Impactful - Kelly M. Kimball; Eric Kiza; Tyler Kimball; Jude Meniru; Michael Rich (Annals of Internal Medicine: Clinical Cases)
Bouveret syndrome is a rare cause of gastric outlet obstruction that arises from a gallstone passing through a choledochoduodenal fistula. It remains poorly understood and is frequently misdiagnosed. We describe a case in which a patient was successfully treated for Bouveret syndrome. The patient presented with recurrent abdominal pain, anorexia, and intractable nausea and vomiting. Esophagogastroduodenoscopy revealed a large, affected stone in the proximal duodenum. The stone was removed via exploratory laparotomy, and the patient was discharged with a prescription for ursodiol. This case aims to serve as a guide to physicians in the early identification of Bouveret syndrome.